Nitro matcha from Copenhagen, Avobagiel from San Francisco, kimchi bowl from Berlin. A pleasure analysis of the Global Brooklyn phenomenon - Kwapisz, Anna (Hybris, 2025)
The article explores the Global Brooklyn phenomenon described by Mateusz Halawa and Fabio Parasecoli, as a cultural formation that is transforming urban gastronomic spaces, making them centralized zones of consumer pleasure and aesthetic experience. Among other things, the author refers to the reflections of Jean Anthelme Brillat-Savarin, pointing out that the practices associated with the production and consumption of food form the foundation of social life, revealing the cultural structures on which everyday life is based. Spaces designed for pleasure become places where locality and individualism are subordinated to global patterns, promoting uniformity of experience and perception. The article analyzes how these spaces, despite their claimed authenticity and pursuit of sensory fulfillment, function within market mechanisms, becoming a tool for controlling how society experiences urban space.